Perancangan Aplikasi Trans Banyumas untuk Pariwisata Menggunakan Metode Agile Scrum - Nabil Hanif Pratama; Irma Barokah; Safira Anggraini Irawan; Muhammad Fauzan Yasykur (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
Tourism in Banyumas Regency holds significant potential with a variety of attractive destinations, and to support tourist access, Trans Banyumas Bus serves as a public transportation mode. Accurate and easily accessible information is key to enhancing the tourist experience. Therefore, this research develops the Android application